Current State of the Art of Newborn Screening for Lysosomal Storage Disorders - David S. Millington; Deeksha S. Bali (MDPI AG, 2018)
Prospective full-population newborn screening for multiple lysosomal storage disorders (LSDs) is currently practiced in a few NBS programs, and several others are actively pursuing this course of action. Two platforms suitable for multiple LSD screening—tandem mass spectrometry (MS/MS) and digital microfluidic fluorometry (DMF)—are now commercially available with reagent kits. In this article, we review the methods currently used for prospective NBS for LSDs and objectively compare their workflows and the results from two programs in the United States that screen for the same four LSDs, one using MS/MS and the other DMF. The results show that the DMF platform workflow is simpler and generates results faster than MS/MS, enabling results reporting on the same day as specimen analysis. Furthermore, the performance metrics for both platforms while not identical, are broadly similar and do not indicate the superior performance of one method over the other. Results show a preponderance of inconclusive results for Pompe and Fabry diseases and for Hurler syndrome, due to genetic heterogeneity and other factors that can lead to low enzyme activities, regardless of the screening method. We conclude that either platform is a good choice but caution that post-analytical tools will need to be applied to improve the positive predictive value for these conditions.